Developers Experience (DX) in ALM Software Tools: An Investigation on Virtual Kanban Boards - Saad, Jullia; Costa, Priscila Portela; Álvaro, Alexandre; Zaina, Luciana A. M. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
In recent years, the work in software engineering has demanded professionals with not only technical but also social skills. Besides, these professionals have struggled to handle the different tools which impact straight in their experience. Among the various tools, virtual kanban boards arise as a tool intensely used by developers. However, little has been investigated about the developers' experience (DX) with these tools. This paper aims to examine the DX of software professionals with virtual kanban boards. We conducted focus group sessions with 10 developers to understand the issues they faced when using these tools. In our analysis, we explored the data gathered from the perspectives of how the developers perceive the resources of the virtual kanban tools, feel about their work, and see the value of their contribution. Our results showed that the developers often struggled in understanding the project scope from the virtual kanban boards they used in their workplace.